Rupture of Hydatid Cyst in the Gallbladder Leading to Acute Cholangitis - Hicham Elmajdoubi; Zakaria Elbarkaoui; Farid Sebbah; Mohamed Raiss; Abdelmalek Hrora (Case Reports in Infectious Diseases)
Hydatid disease is a health problem in endemic areas such as the Mediterranean region caused by Echinococcus granulosus which can develop anywhere in the human body, but it is most frequently located at the liver. Liver hydatid cyst may rupture into the biliary tract, thorax, peritoneum, viscera, digestive tract, or skin, but its rupture in the gallbladder remains rare. We report a rare case of rupture of liver hydatid cyst in the gallbladder leading to acute cholangitis. The diagnosis was suspected on radiological imaging, and the patient was taken to open surgery which confirmed the imaging findings. The gallbladder and adjacent cyst were excised, and a transcystic drain was placed. Postoperative recovery was uneventful.